Not Free at Any Price: Why I switched to the OLPC—and why I dropped it. - Stallman, Richard M. (Boston Review)
The author explores the goals and pitfalls of the One Laptop Per Child (OLPC) project. Initially celebrated as a program that would allow students technological capabilities at a lost cost, the author suggests the program failed when it became a platform for Windows operating system. Free software is discussed. Introducing Microsoft to children, non-free programs, developers, and programmers are commented on in light of the computer from the Lemote company.